Pengembangan Media Pembelajaran Interaktif Menggunakan Platform Padlet pada Materi Norma dalam Kehidupanku di Kelas V SD Negeri 156 Palembang - Putri Wulandari; Siti Dewi Maharani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to develop an interactive learning media based on the Padlet platform on the material Norma in My Life in grade V elementary school and describe its level of validity and practicality. The research method used is Research and Development (R&D) with the ADDIE model which includes the stages of Analyze, Design, Development, and Implementation. At the development stage, learning media is validated by material experts, media experts, and teacher practitioners. The validation results showed that the developed media had a very high level of validity with a percentage of 95.8% of material experts, 94.2% of media experts, and 100% of teacher practitioners. After revision based on the validator's suggestions, this media is implemented to students through individual, small group, and large group trials. The results of the trial show that this medium is very practical with an average percentage of practicality of 100%. In conclusion, Padlet-based learning media in the Norma in My Life material is very valid and very practical to be used in learning. This media facilitates more interactive, flexible learning, and increases student involvement in the learning process.